GLOBAL – LOKAL : ADAPTASI BUDAYA FILM INTERNASIONAL - ., Saepudin (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2012)
Film is the modern cultural product. It is always influenced by values and culture where it is produced. As one of media product, surely film is not distributed only for local market, but served for international society too. Internationalfilms for certain nations are not accepted directly, it must be censored by state organization which will judge that films. Censorship is one kind of cultural adaptation by means of organization. This research, studies process of censorship by Malaysia Censorship Organization (LPF) to Indonesia?s film which is distributed in Malaysia. The researcher use semiotics to analyze it. Then it was found that even Indonesia and Malaysia have various similiarity in culture, it is not mean cultural product can be accepted directly. Indonesia?s film was censored by LPF for content of sexual and violence.